RUSSIAN MILITARY AGGRESSION IN UKRAINE: POSSIBLE SCENARIOS AND WAYS OF CONFLICT SETTLEMENT - Зельманович, І. І. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
The article deals with the problem of Russian military aggression in Ukraine, which resulted in the annexation of Crimea and the occupation of the parts of the districts of Donetsk and Lugansk regions. The article focuses on the issue of identifying the goals and objectives pursued by the Russian Federation in the confrontation zone, as well as analysing possible scenarios and ways of resolving the conflict in the east and south of Ukraine. In particular, three possible scenarios for the development of events in Donbass are taken as the basis – that’s "Croatian", "Moldovan" and "German" scenarios, and the pros and cons of each of these approaches, and the consequences that they may have for Ukraine are analysed in detail. The article states that the conflict in the east of Ukraine is gaining more and more signs of a "frozen" confrontation, which Russia actually seeks to reach. After all, when analysing the strategic plans of the Russian state, which it tries to implement from the beginning of the 1990s, they look quite obvious: to create around a series of "frozen" conflicts, which will allow it, on the one hand, to control the actions and policies of its neighbouring states, and on the other hand, it thus destroys all aspects of the international order, and undermines the security stability around the world. So, Ukraine must develop an effective strategy for the liberation of all the occupied Ukrainian territories. In our opinion, it is necessary to analyse the history and problematic issues of other conflicts that exist on the territory of the post-Soviet space and which directly involve the Russian Federation (primarily the Transnistrian crisis, the problems of Nagorno-Karabakh, Abkhazia and South Ossetia). Also, after stabilizing the military situation on the collision line, it is extremely important today to intensify work in two other areas: first of all, it is an internal direction, which involves a whole range of actions and measures, the most important of which, in our opinion, is overcoming the systemic crisis of governmental and public relations, fighting corruption, economic development, raising the social standards of living of the population. The other, not less important is active foreign policy and diplomatic work, because in a hybrid confrontation, it is extremely important not to give in to Russia not only in military terms, but also in the information confrontation and struggle in the international arena.